(untitled) (Bangladesh Journal of Medical Science, 2025)
Duchenne muscular dystrophy is an inherited neuromuscular disorder that follows an X-linked recessive pattern of inheritance. It manifests as a severe condition characterized by progressive muscle degeneration due to mutations in the DMD gene, which is responsible for encoding the dystrophin protein. Objective To assess clinical changes in children with Duchenne myodystrophy from the type of DMD gene mutation. Material and methods The study involved 97 boys aged from 3 to 15 years, the average age of onset of the disease was 3.2±0.18 years. To study patients, laboratory research methods were used, such as a biochemical blood test (creatinine phosphokinase level), and a search for a genetic mutation in the DMD gene was carried out using MLPA and NGS. Clinical manifestations of this disease were assessed using functional status scales. Results Among the children studied, MLPA revealed deletions in 56 (57.5%), large duplications in 13 (13.2%), and point mutations in 28 (29.3%). The remaining mutations were situated closer to the terminal part responsible for the linkage of the dystroglycanprotein complex within the muscle framework. Conclusion In our investigation, we explored the correlations between primary clinical data and different mutation characteristics. Our analysis revealed a significant and reliable association between early loss of independent movement, as well as early disease onset, and mutations capable of disrupting the translational reading frame of the dystrophin protein. Given that neuromuscular diseases, including genetic disorders, represent a pressing issue in clinical neurology, these findings underscore the importance of understanding such correlations in managing these conditions. Bangladesh Journal of Medical Science Vol. 24 No. 01 January’25 Page : 279-284